Doing Research in a Conflict Situation Encounters and Experiences - Dhakal, Suresh (Dhaulagiri Journal of Sociology and Anthropology, 2014)
Fieldwork, an anthropologist's vocation, is full of tensions and dilemmas. However, the experiences of any or all tensions, troubles and even failures are a 'source of ethnographic knowledge in themselves'. During the fieldwork for my PhD research, I encountered several such incidents, which have made my work more interesting and my experience richer. This article describes the situation of doing fieldwork in the conflict period, when the 'peace process' was not yet come to the conclusion. DOI: http://dx.doi.org/10.3126/dsaj.v8i0.10723 Dhaulagiri Journal of Sociology and Anthropology Vol. 8, 2014; 87-98